ANALYSIS OF THE PROBLEMS IN DIGITALIZATION OF THE HOTEL SYSTEM AND THE RESEARCHES OF ECONOMISTS WHO CONDUCTED SCIENTIFIC WORK IN THIS FIELD - M.M. Murtolibova (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: The incomplete digitization systems in Uzbekistan’s hotel industry result in operational inefficiencies, low-quality services, and guest dissatisfaction, particularly from foreign visitors. Key issues include a lack of ICT specialists, inadequate infrastructure, and insufficient digital skills among management and staff. Methods: This study analyzes expert recommendations and existing models, including Ye.I. Lizunova’s organizational mechanisms and M.F. Melekhov’s innovative strategies, to propose solutions for modernizing the industry. Grouping methods and infrastructure evaluations are emphasized to improve legal and organizational frameworks. Results: Findings reveal significant gaps in digital skills, lack of international collaborations, and outdated technologies as primary factors hindering growth. Adoption of advanced ICT training, enhanced service infrastructure, and strategic international partnerships are identified as critical to improving hotel operations and global competitiveness. Novelty: The study proposes an integrated approach combining targeted personnel training, innovative technologies, and collaborative strategies with international organizations to address the unique challenges faced by Uzbekistan’s hospitality sector. These measures can align the industry with global standards and ensure sustainable growth.